STUDENTS’ EXPERIENCES OF LEARNING ENGLISH IN INDONESIA: SOME EFFECTIVE AND INEFFECTIVE WAYS - Azhar Aziz Lubis; Nopriansah Nopriansah; Abdul Halim; Sukma Septian Nasution; Muhammad Yusuf (Abjadia, 2018)
Although the study of effective strategies for teaching English as a foreign language (TEFL) in Indonesia has become prominent research topics for decades, little attention is paid to the students’ experiences of learning English. This study aims at researching some of our students’ experiences of learning English both at their junior and senior high schools. The students reflecting the experience were participants of our course unit of General English, Introduction to linguistics, Structure 2, History of English language, and were both from non-English and English departments at the University of Bengkulu and Dehasen University, Bengkulu, Indonesia. Of the eight effective and fourteen ineffective ways to learn English, we found three main issues apparent in our study namely self-confidence and motivation, learning environment, and methods and media in teaching English as a foreign language. Further explication of each issue is discussed.على الرغم من أن دراسة الاستراتيجيات الفعالة لتدريس اللغة الإنجليزية كلغة أجنبية (TEFL) في إندونيسيا أصبحت موضوعات بحثية بارزة لعقود من الزمن، إلا أنه لم يتم إيلاء اهتمام كبير لخبرات الطلاب في تعلم اللغة الإنجليزية. تهدف هذه الدراسة إلى البحث في بعض تجارب طلابنا في تعلم اللغة الإنجليزية في مدارسهم الثانوية والإعدادية. كان الطلاب الذين يعكسون التجربة مشاركين في وحدة دوراتنا في اللغة الإنجليزية العامة، ومقدمة في اللغويات، والهيكل 2، وتاريخ اللغة الإنجليزية، وكانوا من أقسام غير الإنجليزية والإنجليزية في جامعة بنجكولو وجامعة ديهاسين، بنجكولو، إندونيسيا. من بين الطرق الثمانية الفعالة والأربعة عشر غير الفعالة لتعلم اللغة الإنجليزية، وجدنا ثلاث قضايا رئيسية واضحة في دراستنا وهي الثقة بالنفس والتحفيز، والبيئة التعليمية ، والأساليب ووسائل الإعلام في تدريس اللغة الإنجليزية كلغة أجنبية. مناقشة المزيد من شرح كل قضية.